Safeguards Assessment : 2017 Update. (Policy Papers; Policy Paper ;, 2017)
activity remained consistent with recent years. 21 assessments were completed during the update period (September 2015-April 2017) and five were in progress at the end of the period. Activity continues to average around 13 assessments per year. While the number of central banks under monitoring decreased slightly from 67 to 63, some monitoring cases required intense engagement due to safeguards challenges that emerged. These related to forensic investigations, governance reforms, and a deterioration in safeguards frameworks of central banks facing difficult external conditions.